Co-existence of airborne SARS-CoV-2 infection and non-infection in three connected zones of a restaurant - Wei Jia; Qun Wang; David Christopher Lung; Pak-To Chan; Peihua Wang; Edwin Chung-Hin Dung; Tiffany Didik; Garnet Kwan-Yue Choi; Herman Tse; Yijie Wu; Te Miao; Wenzhao Chen; et al. (Journal of Hazardous Materials, 2024)

Unveiling the urban resilience in cities of China, a study on NO2 concentrations and COVID-19 pandemic - Shaolin Wu; Man Sing Wong; Baofeng Di; Xiaoli Ding; Guoqiang Shi; Edwin H.W. Chan; Waqas Muhammad (Atmospheric Environment, 2024)

The impact of rice-crayfish field on socio-ecological system in traditional farming areas: Implications for sustainable agricultural landscape transformation - Youlin Chen; Peiheng Yu; Lei Wang; Yiyun Chen; Edwin Hon Wan Chan (Journal of Cleaner Production, 2024)

Simulation of vertical dispersion and pollution impact of artificial light at night in urban environment - Jimmy C.K. TONG; Anthonio H.L. WUN; Thomas T.H. CHAN; Edmond S.L. LAU; Edwin C.F. LAU; Hahn H.K. CHU; Arthur P.S. LAU (Science of The Total Environment, 2023)

An integrated approach for examining urban fragmentation in metropolitan areas: Implications for sustainable urban planning - Peiheng Yu; Esther H.K. Yung; Edwin H.W. Chan; Man Sing Wong; Siqiang Wang; Yiyun Chen (Journal of Cleaner Production, 2023)

Open space fragmentation in Hong Kong's built–up area: An integrated approach based on spatial horizontal and vertical equity lenses - Peiheng Yu; Edwin H.W. Chan; Esther H.K. Yung; Man Sing Wong; Yiyun Chen (Environmental Impact Assessment Review, 2023)

Cycles of heat exposure elevate metabolic enzyme genes and alters digestion in mussels - Grace Chan; Andrew Y. Gracey; Edwin Solares; Beck A. Wehrle; Kwasi M. Connor (Frontiers in Marine Science, 2023)
The intertidal sea mussel Mytilus californianus inhabits the Pacific coastline of North America. As a sessile organism it must cope with daily fluctuations of the marine and terrestrial environments. Organisms in stressful environments are commonly faced with energetic trade-offs between somatic and reproductive growth and stress management. Although, this energetic theory is generally accepted for mussels as well, the spectrum of mechanisms underlying this framework have not been widely investigated. In the current study we hypothesized that mussels acclimated to a cyclical moderately warm aerial environment would display enhanced transcript abundance of genes related to metabolism and exhibit resilient digestive enzyme activity (energy acquisition). Following acclimation to simulated tidal regimes in the laboratory we observed higher gene-expression of citrate synthase ( CS ), citrate lyase ( ACLY ), and mammalian target of rapamycin ( MTOR ) in heat stressed mussels. The expression of CS and MTOR was not elevated under acute thermal stress, suggestive that repeated stress is required for robust expression of these genes given that all other environmental variables are constant. We also observed reduced activity of the digestive enzyme, amylase in heat-shocked acclimated mussels (a proxy for energy acquisition). Our results suggest that mussels that settle high on shore not only face the challenge of thermal stress repair and limited access to food but may also be compromised by reduced digestive performance. Mussels may have adapted to cyclical energetic stress by overexpressing particular energy-related genes that can mitigate the disturbance to energy balance once the abundant transcripts are translated into functional proteins.

Standards of Fluid Biomarker Collection and Pre-analytical Processes in Humans and Mice: Recommendations by the Ataxia Global Initiative Working Group on Biomarkers - Filippo M. Santorelli; Hayley S. McLoughlin; Justin M. Wolter; Daniele Galatolo; Matthis Synofzik; David Mengel; Puneet Opal; Antonijevic Irina; Auburger Georg; Bataller Luis; Bertini Enrico; Boesch Sylvia; et al. (The Cerebellum, 2023)

Capturing open space fragmentation in high–density cities: Towards sustainable open space planning - Peiheng Yu; Esther H.K. Yung; Edwin H.W. Chan; Siqiang Wang; Youlin Chen; Yiyun Chen (Applied Geography, 2023)

Consensus Recommendations for Clinical Outcome Assessments and Registry Development in Ataxias: Ataxia Global Initiative (AGI) Working Group Expert Guidance - Thomas Klockgether; Matthis Synofzik; Saud Alhusaini; Mathieu Anheim; Irina Antonijevic; Tee Ashizawa; Luis Bataller; Mélanie Berard; Enrico Bertini; Sylvia Boesch; Pedro Braga-Neto; Emanuel Cassou; et al. (The Cerebellum, 2023)
To accelerate and facilitate clinical trials, the Ataxia Global Initiative (AGI) was established as a worldwide research platform for trial readiness in ataxias. One of AGI’s major goals is the harmonization and standardization of outcome assessments. Clinical outcome assessments (COAs) that describe or reflect how a patient feels or functions are indispensable for clinical trials, but similarly important for observational studies and in routine patient care. The AGI working group on COAs has defined a set of data including a graded catalog of COAs that are recommended as a standard for future assessment and sharing of clinical data and joint clinical studies. Two datasets were defined: a mandatory dataset (minimal dataset) that can ideally be obtained during a routine clinical consultation and a more demanding extended dataset that is useful for research purposes. In the future, the currently most widely used clinician-reported outcome measure (ClinRO) in ataxia, the scale for the assessment and rating of ataxia (SARA), should be developed into a generally accepted instrument that can be used in upcoming clinical trials. Furthermore, there is an urgent need (i) to obtain more data on ataxia-specific, patient-reported outcome measures (PROs), (ii) to demonstrate and optimize sensitivity to change of many COAs, and (iii) to establish methods and evidence of anchoring change in COAs in patient meaningfulness, e.g., by determining patient-derived minimally meaningful thresholds of change.

Standards of NGS Data Sharing and Analysis in Ataxias: Recommendations by the NGS Working Group of the Ataxia Global Initiative - Danique Beijer; Brent L. Fogel; Sergi Beltran; Matt C. Danzi; Andrea H. Németh; Stephan Züchner; Matthis Synofzik; Astrid Adarmes; Saud Alhusaini; Mahmoud Reza Ashrafi; Luis Bataller; Enrico Bertini; et al. (The Cerebellum, 2023)
The Ataxia Global Initiative (AGI) is a worldwide multi-stakeholder research platform to systematically enhance trial-readiness in degenerative ataxias. The next-generation sequencing (NGS) working group of the AGI aims to improve methods, platforms, and international standards for ataxia NGS analysis and data sharing, ultimately allowing to increase the number of genetically ataxia patients amenable for natural history and treatment trials. Despite extensive implementation of NGS for ataxia patients in clinical and research settings, the diagnostic gap remains sizeable, as approximately 50% of patients with hereditary ataxia remain genetically undiagnosed. One current shortcoming is the fragmentation of patients and NGS datasets on different analysis platforms and databases around the world. The AGI NGS working group in collaboration with the AGI associated research platforms—CAGC, GENESIS, and RD-Connect GPAP—provides clinicians and scientists access to user-friendly and adaptable interfaces to analyze genome-scale patient data. These platforms also foster collaboration within the ataxia community. These efforts and tools have led to the diagnosis of > 500 ataxia patients and the discovery of > 30 novel ataxia genes. Here, the AGI NGS working group presents their consensus recommendations for NGS data sharing initiatives in the ataxia field, focusing on harmonized NGS variant analysis and standardized clinical and metadata collection, combined with collaborative data and analysis tool sharing across platforms.

The photometric observation of the quasi-simultaneous mutual eclipse and occultation between Europa and Ganymede on 22 August 2021 - Chu Wing So; Godfrey Ho Ching Luk; Giann On Ching Chung; Po Kin Leung; Kenneith Ho Keung Hui; Jack Lap Chung Cheung; Ka Wo Chan; Edwin Lok Hei Yuen; Lawrence Wai Kwan Lee; Patrick Kai Ip Lau; Gloria Wing Shan Cheung; Prince Chun Lam Chan; et al. (Icarus, 2023)

On the urban compactness to ecosystem services in a rapidly urbanising metropolitan area: Highlighting scale effects and spatial non–stationary - Peiheng Yu; Shujin Zhang; Esther H.K. Yung; Edwin H.W. Chan; Bo Luan; Yiyun Chen (Environmental Impact Assessment Review, 2023)

Striatal dopamine synthesis capacity and its association with negative symptoms upon resolution of positive symptoms in first-episode schizophrenia and delusional disorder - Stephanie M. Y. Wong; Y. N. Suen; Charlotte W. C. Wong; Sherry K. W. Chan; Christy L. M. Hui; W. C. Chang; Edwin H. M. Lee; Calvin P. W. Cheng; Garrett C. L. Ho; Gladys Goh Lo; Eric Y. L. Leung; Paul K. M. Au Yeung; et al. (Psychopharmacology, 2022)

Demonstration of Direct Nose-to-Brain Transport of Unbound HIV-1 Replication Inhibitor DB213 Via Intranasal Administration by Pharmacokinetic Modeling - Qianwen Wang; Yufeng Zhang; Chun-Ho Wong; H.Y. Edwin Chan; Zhong Zuo (The AAPS Journal, 2018)

Identification of receptor-type protein tyrosine phosphatase μ as a new marker for osteocytes - Karien E. de Rooij; Martijn van der Velde; Edwin de Wilt; Martine M. L. Deckers; Martineke Bezemer; Jan H. Waarsing; Ivo Que; Alan. B. Chan; Eric L. Kaijzel; Clemens W. G. M. Löwik (Histochemistry and Cell Biology, 2015)

Refinement of schizophrenia GWAS loci using methylome-wide association data - Gaurav Kumar; Shaunna L. Clark; Joseph L. McClay; Andrey A. Shabalin; Daniel E. Adkins; Linying Xie; Robin Chan; Srilaxmi Nerella; Yunjung Kim; Patrick F. Sullivan; Christina M. Hultman; Patrik K. E. Magnusson; et al. (Human Genetics, 2015)

Proof-of-concept randomized controlled trial of pregnenolone in schizophrenia - Christine E. Marx; Jimmy Lee; Mythily Subramaniam; Attilio Rapisarda; Dianne C. T. Bautista; Edwin Chan; Jason D. Kilts; Robert W. Buchanan; Eu Pui Wai; Swapna Verma; Kang Sim; Jayaraman Hariram; et al. (Psychopharmacology, 2014)

Expression of Expanded CAG Transcripts Triggers Nucleolar Stress in Huntington's Disease - Ho Tsoi; Ho Yin Edwin Chan (The Cerebellum, 2013)

Sesamin extends the mean lifespan of fruit flies - Yuanyuan Zuo; Cheng Peng; Yintong Liang; Ka Ying Ma; Ho Yin Edwin Chan; Yu Huang; Zhen-Yu Chen (Biogerontology, 2013)

Site-Specific Tryptophan Oxidation Induced by Autocatalytic Reaction of Polysorbate 20 in Protein Formulation - Xanthe M. Lam; William G. Lai; Edwin K. Chan; Victor Ling; Chung C. Hsu (Pharmaceutical Research, 2011)

Achieving High Research Reporting Quality Through the Use of Computational Ontologies - Amrapali Zaveri; Luciana Cofiel; Jatin Shah; Shreyasee Pradhan; Edwin Chan; Olivier Dameron; Ricardo Pietrobon; Beng Ti Ang (Neuroinformatics, 2010)

Design considerations for environmental sustainability in high density development: a case study of Hong Kong - Edwin H. W. Chan; Grace K. L. Lee (Environment, Development and Sustainability, 2009)

Transcriptional malfunctioning of heat shock protein gene expression in spinocerebellar ataxias - N. Y. Macy Huen; S. L. Alan Wong; H. Y. Edwin Chan (The Cerebellum, 2007)